2017
DOI: 10.1101/lm.045542.117
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological correlates of state-dependent context fear

Abstract: Retrieval of fear memories can be state-dependent, meaning that they are best retrieved if the brain states at encoding and retrieval are similar. Such states can be induced by activating extrasynaptic γ-aminobutyric acid type A receptors (GABAR) with the broad α-subunit activator gaboxadol. However, the circuit mechanisms and specific subunits underlying gaboxadol's effects are not well understood. Here we show that gaboxadol induces profound changes of local and network oscillatory activity, indicative of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…For example, while theta rhythm is a dominant pattern of local field potential (LFP) during voluntary behavior as well as rapid-eye-movement (REM) sleep 12 , 13 , delta oscillations are the hallmark of deep sleep, contributing to memory consolidation 14 , 15 . Moreover, recent study has also shown that GABA A receptor agonist gaboxadol, a previously proved state-dependent learning inducing drug, significantly enhances hippocampal delta power 5 , 16 , suggesting brain oscillations may be associated with the phenomenon of state-dependent memory.…”
Section: Introductionmentioning
confidence: 92%
“…For example, while theta rhythm is a dominant pattern of local field potential (LFP) during voluntary behavior as well as rapid-eye-movement (REM) sleep 12 , 13 , delta oscillations are the hallmark of deep sleep, contributing to memory consolidation 14 , 15 . Moreover, recent study has also shown that GABA A receptor agonist gaboxadol, a previously proved state-dependent learning inducing drug, significantly enhances hippocampal delta power 5 , 16 , suggesting brain oscillations may be associated with the phenomenon of state-dependent memory.…”
Section: Introductionmentioning
confidence: 92%
“…Changes in the hippocampus, which is known to play important roles in processing both conscious and unconscious memories (Henke, 2010 ; Hannula and Greene, 2012 ; Shohamy and Turk-Browne, 2013 ), may be particularly relevant. A notable change within the hippocampus and cortex during SDM encoding under heightened tonic inhibition (using systemic infusion of the drug gaboxadol) is the increase in power of slow, delta oscillations, along with a decrease of theta and gamma oscillations (Meyer et al, 2017 ). At the same time, at the circuit level, the connectivity between the hippocampus and neocortical areas (retrosplenial, entorhinal and anterior cingulate cortex) is significantly reduced (Jovasevic et al, 2015 ; Meyer et al, 2017 ).…”
Section: Memory and Sdm—a Neurobiological Perspectivementioning
confidence: 99%
“…A notable change within the hippocampus and cortex during SDM encoding under heightened tonic inhibition (using systemic infusion of the drug gaboxadol) is the increase in power of slow, delta oscillations, along with a decrease of theta and gamma oscillations (Meyer et al, 2017 ). At the same time, at the circuit level, the connectivity between the hippocampus and neocortical areas (retrosplenial, entorhinal and anterior cingulate cortex) is significantly reduced (Jovasevic et al, 2015 ; Meyer et al, 2017 ). Consistent with these observations, it was recently found that enhanced cortical delta oscillations causally contribute to the formation of state-dependent fear-inducing context memories during states of reduced excitation (using systemic administration of the NMDA receptor antagonist MK-801; Jiang et al, 2018 ).…”
Section: Memory and Sdm—a Neurobiological Perspectivementioning
confidence: 99%
“…Rodent models of stress-enhanced state-dependent fear conditioning (S-SDFC) and state-dependent fear conditioning (SDFC) allow studying the impact of stressrelated memories on social behavior. Whereas increasing stress exposure strengthens the encoding of fear-inducing memory [9][10][11][12][13] , state-dependent encoding restricts memory access to specific brain states 14,15 . State-dependent memory is readily induced in mice trained on gaboxadol (GBX), an agonist of extrasynaptic GABA A R 16 that enhances tonic inhibition in the DG 17 .…”
Section: Introductionmentioning
confidence: 99%
“…State-dependent memory is readily induced in mice trained on gaboxadol (GBX), an agonist of extrasynaptic GABA A R 16 that enhances tonic inhibition in the DG 17 . Although such memories are normally not accessible to retrieval, their presence can be demonstrated when mice are tested in the presence of the drug 14 , 15 . Furthermore, in this model, stress-related fear memories seem to be inhibited by cortical mechanisms and preferentially processed by hippocampal–lateral septal (LS) circuits 14 .…”
Section: Introductionmentioning
confidence: 99%